Are optical disks suitable for long-term preservation - Stančić, Hrvoje; Tušek, Mladen; Rajh, Arian (2008)
Quantity of information that surrounds us is increasing every day. The abilities to process and store information, as well as the ability to retrieve information, have become much more challenging. We have accepted ascendance of reposing information in the electronic environment for daily usage. We have observed different solutions of processing and retrieving information from assorted databases, expert systems and networks. Because of this different approaches and solutions, the authors thought that it was necessary to set up a survey in the domain of information storage. Of great concern is the fact that today we still cannot predict or guarantee endurance of relatively big quantity of information in the electronic form for the period of, for example, ten years from now. Rapid technological development, or confinements in the other hand, forces us to migrate the content without respite, check over readability of that content, make multiple copies and so forth. These issues can apply to the case of optical discs as information carriers. In the last few years, industry declared optical discs as a very liable media for storage of large amounts of information. This research was set up to acquire or to verify certain facts about reliability of this kind of storage, to establish methods that could ensure higher reliability of optical discs and to reduce risk from losing useful and important information. The authors conducted a research and focused on the sample of electronic records on optical carriers in possession of Croatian Agency for Medicinal Products and Medical Devices. This institution is a good example of the record holder of today – it gathers electronic documentation from various sources and it has a mission to preserve it for the long term. Optical discs contain business information that various clients recorded with different applications and versions and then submitted to the Agency at different times. Not all disc carriers could be included in the survey. Therefore, a smaller but representative sample was analyzed. That is why an equal number of media for every manufacturer declared was selected for every period of production. Commercially available computer programs were used in attempt to fortify the real manufacturer of media, type of disc, type of chemical layer contained inside, date of recording, version of application in which the content was recorded, and finally, current condition of optical discs. For the practical reasons, the authors wanted to know what sort of discs clients prefer for information storage and for submitting it to the Agency. Further, the authors wanted to find out what is the relationship between chemical layer and readability of information stored after a long-term period, layer and insusceptibility to ageing, layer and resistance to microclimatic conditions, and ratio of usage of specific layer. Finally, they link together all the variables identified with this survey and then make recommendations for the future storage and usage of optical carriers as a long-term storage solution thus showing what are advantages and disadvantages of optical storage systems.
Projekt MZOS
ENG